Abnormal Calcium Handling in Duchenne Muscular Dystrophy: Mechanisms and Potential Therapies - Mareedu, Satvik; Million, Emily D.; Duan, Dongsheng; Babu, Gopal J. (Frontiers in Physiology, 2021)
Duchenne muscular dystrophy (DMD) is an X-linked muscle-wasting disease caused by the loss of dystrophin. DMD is associated with muscle degeneration, necrosis, inflammation, fatty replacement, and fibrosis resulting in muscle weakness, respiratory and cardiac failure, and premature death. There is no curative treatment. Investigations on disease-causing mechanisms offer an opportunity to identify new therapeutic targets to treat DMD. An abnormal elevation of the intracellular calcium (Ca2+i) concentration in the dystrophin-deficient muscle is a major secondary event, which contributes to disease progression in DMD. Emerging studies have suggested that targeting Ca2+ handling proteins and/or mechanisms could be a promising therapeutic strategy for DMD. Here, we provide an updated overview of the mechanistic roles the sarcolemma, sarco/endoplasmic reticulum, and mitochondria play in the abnormal and sustained elevation of Ca2+i levels and their involvement in DMD pathogenesis. We also discuss current approaches aimed at restoring Ca2+ homeostasis as potential therapies for DMD.